Mining and Mineral Exploration Projects within the Natura 2000 Area: Case Studies from Northern Finland - Toni Eerola; Nike Luodes; Hannu Panttila (Materials Proceedings, 2024)
The Rompas–Prajapat (Au-Co) and Sakatti (Ni-Cu-PGE) mineral deposits are among the only important discoveries of the last few decades in Finland. Both are partially located in Natura 2000 areas, which are among the most sensitive land use contexts in which mining and mineral disputes have emerged in Finland. Consequently, the project holders apply low-impact mineral exploration technologies and practice active stakeholder engagement and communication. In fact, projects seem to be mostly favored by local populations. However, because of their association with protected areas (and uranium in the case of Rompas), projects are opposed by non-governmental organizations, as well as by reindeer herders in the case of Sakatti. Project holders perform feasibility studies and environmental impact assessments. Mining licenses are applied under a new Finnish mining act and the European Union’s Raw Materials acts.